Dose-Distribution-Driven PET Image-Based Outcome Prediction (DDD-PIOP): A Deep Learning Study for Oropharyngeal Cancer IMRT Application - Wang, Chunhao; Liu, Chenyang; Chang, Yushi; Lafata, Kyle; Cui, Yunfeng; Zhang, Jiahan; Sheng, Yang; Mowery, Yvonne; Brizel, David; Yin, Fang-Fang (Frontiers in Oncology, 2020)
Purpose: To develop a deep learning-based AI agent, DDD-PIOP (Dose-Distribution-Driven PET Image Outcome Prediction), for predicting 18FDG-PET image outcomes of oropharyngeal cancer in response to intensity-modulated radiation therapy (IMRT). Methods: DDD-PIOP uses pre-radiotherapy 18FDG-PET/CT images and the planned spatial dose distribution as the input, and it predicts the 18FDG-PET image outcomes in response to the planned IMRT delivery. This AI agent centralizes a customized convolutional neural network (CNN) as a deep learning approach, and it incorporates a few designs to enhance prediction accuracy. 66 oropharyngeal cancer patients who received IMRT treatment on a sequential boost regime (2Gy/ daily fraction) were studied for DDD-PIOP development. 61 patients were used for AI agent training/validation, and the remaining 5 were used as independent tests. To evaluate the developed AI agent’s performance, the predicted mean standardized uptake values (SUVs) of gross tumor volume (GTV) and clinical target volume (CTV) were compared with the ground truth values. Overall SUV distribution accuracy was evaluated by gamma test passing rates under different criteria. Results: The developed DDD-PIOP successfully generated 18FDG-PET image outcome predictions for 5 test patients. The predicted mean SUV values of GTV/CTV were 3.50/1.41, which were close to the ground-truth values of 3.57/1.51. In 2D-based gamma tests, the average passing rate was 92.1% using 5%/10mm criteria, which was improved to 95.9%/93.2% when focusing on GTV/CTV regions. 3D gamma test passing rates were 98.7% using 5%/10mm criteria, and the corresponding GTV/CTV results were 99.8%/99.4 %. Conclusion: The reported results suggest that the developed AI agent DDD-PIOP successfully predicted 18FDG-PET image outcomes with high quantitative accuracy. The generated voxel-based image outcome predictions could be used for treatment planning optimization prior to radiation delivery for the best individual-based outcome.